2D Layered Material Alloys: Synthesis and Application in Electronic and Optoelectronic Devices. Issue 1 (31st October 2021) - Yao, Jiandong; Yang, Guowei
Abstract: 2D layered materials (2DLMs) have come under the limelight of scientific and engineering research and broke new ground across a broad range of disciplines in the past decade. Nevertheless, the members of stoichiometric 2DLMs are relatively limited. This renders them incompetent to fulfill the multitudinous scenarios across the breadth of electronic and optoelectronic applications since the characteristics exhibited by a specific material are relatively monotonous and limited. Inspiringly, alloying of 2DLMs can markedly broaden the 2D family through composition modulation and it has ushered a whole new research domain: 2DLM alloy nano‐electronics and nano‐optoelectronics. This review begins with a comprehensive survey on synthetic technologies for the production of 2DLM alloys, which include chemical vapor transport, chemical vapor deposition, pulsed‐laser deposition, and molecular beam epitaxy, spanning their development, as well as, advantages and disadvantages. Then, the up‐to‐date advances of 2DLM alloys in electronic devices are summarized. Subsequently, the up‐to‐date advances of 2DLM alloys in optoelectronic devices are summarized. In the end, the ongoing challenges of this emerging field are highlighted and the future opportunities are envisioned, which aim to navigate the coming exploration and fully exert the pivotal role of 2DLMs toward the next generation of electronic and optoelectronic devices. Abstract : A comprehensive overview on the synthesis of 2D layered material alloys, as well as, the corresponding electronic and optoelectronic devices is provided. In addition, the ongoing challenges are highlighted and the future opportunities are envisioned, which aim to navigate the coming exploration and fully exert the pivotal role of 2D materials toward the next generation of electronic and optoelectronic devices.